Self-Confidence dan Pemaknaan Hijrah bagi Muslim dilihat dari Persfektip Konseling Islam - Langgeng Sutopo; Heru Masfiyatul Asriyah; M. Ari Wibowo; Hernisawati Hernisawati (Kuras Institute, 2022)
Students with positive self-esteem tend to be confident, easy to make friends, happy, optimistic, have high motivation both academically and non-academicly, dare to take risks, are independent, responsible and achieve The meaning of hijrah is also a trend to show off that it has routine activities that are useful not on the basis of the heart's movement to change, then the meaning of hijrah is also limited to changing clothes that are more closed and more arrogant, of course this has the wrong meaning. Full meaning of something will certainly produce good conclusions, especially on the meaning of hijrah. Having the wrong meaning of hijrah that is not in accordance with Islamic values ​​will certainly make a teenager who does not have a positive self-concept.